An Experimental Study of the Influences of Lacquer Thinner Addition to Gasoline on Performance and Emissions of a Spark Ignition Engine - Ahmet Uyumaz; Ali Batuhan Kilmen; Murat Kaş (Engineering Perspective)
In this study, lacquer thinner (LT) has been utilized as an addition to pure gasoline in a single cylinder SI engine for increasing performance and reducing emissions. The tests were done at wide open throttle condition and 2400, 2700, 3000, 3300, 3600 and 3900 rpm engine speeds. The influences of lacquer thinner were observed on the engine torque, thermal efficiency, specific fuel consumption (SFC) and HC, CO and CO2 emissions. The findings demonstrated that with the addition of the lacquer thinner caused engine torque and power output values to decrease as the amount of lacquer thinner increased. SFC was increased by about 4.36%, 9.13% and 11.64% with LT10, LT20 and LT30 compared to full gasoline at 2700 rpm respectively. But fairly noticeable reductions were observed at CO and HC emissions as lacquer thinner added to the gasoline. HC decreased by 3.4%, 5.6% and 12.13% with LT10, LT20 and LT30 according to gasoline at 3900 rpm respectively. Similarly, CO has decreased by 1.09%, 2.18% and 3.56% with LT10, LT20 and LT30 according to gasoline at 3900 rpm respectively. Lacquer thinner showed positive and impressive results compared to pure gasoline on exhaust emissions. However thermal efficiency decreased, and SFC has in-creased with lacquer thinner addition to gasoline, but the reduction in engine torque and power can be acceptable considering the drastic improvements at emission levels. Also, it has been observed that lacquer thinner can be used as a gasoline additive without any modifications in spark ignition engines. Still further research is needed on Lacquer thinner on SI engines.